IMPLEMENTASI KURIKULUM DALAM MANAJEMEN BERBASIS SEKOLAH SEBAGAI UPAYA MENINGKATKAN MUTU PENDIDIKAN SEKOLAH DASAR - Jaihan Safitri; Rusi Rusmiati Aliyyah; Awaludin Abdul Gaffar (AL - KAFF: JURNAL SOSIAL HUMANIORA, 2022)
The cause of the quality of education did not increase evenly when viewed from the system there were indeed problems, there were several factors that the researchers summarized, namely: the policy and implementation of national education, the need to be given great autonomy to schools accompanied by the responsible school management. This study aims to determine the Implementation Curriculum of School-Based Management as an Effort to Improve the Quality of Elementary School Education in SDN Pasawahan Cicurug. This research was conducted at SDN Pasawahan Cicurug Sukabumi District using qualitative methods with the type of case study research. Data collection techniques are done through observation, interviews, and documentation. Data analysis using the Miles and Huberman model which consists of data collection, data reduction, data presentation, and verification, or conclusion. Checking the validity of the data using the triangulation of data sources. The results showed: (1) The implementation of SBM at SDN Pasawahan Cicurug had been well implemented and had met standards that were professionally organized through school management by producing superior and high-quality school management units; (2) 2013 curriculum is carried out as a whole, both the implementation of learning using a thematic approach with curriculum settings and learning with the characteristics of applying culture or habits of curriculum literacy with school-based learning; (3) The relationship between the school and the community at SDN Pasawahan Cicurug includes activities, the participation of parents and the community, the school committee, and DUDI based on the principles of implementing school-based management. This research is limited by curriculum implementation and school relations with the community.